Recent developments and novel applications of thin film, light‐emitting transistors - Zaumseil, Jana (Advanced functional materials, 2020)
Light‐emitting field‐effect transistors are optoelectronic devices that combine switching and amplification with light emission. They can be created with a wide range of semiconductors from organic to inorganic and nanoscale.